Network Governance Towards Development Policy of Podokoyo Tourism Village in Pasuruan regency - Sulung Satriyo Irkham Pambudi; Muhammad Luthfil Hakim; Very Yudha Lesmana (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
This article explores the network governance in the development of the Podokoyo Tourism Village, Pasuruan Regency. This study aims to analyze the application of the elements of network governance, which include trust, network goal consensus, need for network-level competencies, the number of participants, outputs, and outcomes of tourism Village development. The study results identify three achievements during the Podokoyo Tourism Village development network, such as the success of having superior Village products, increasing the capacity of Podokoyo Village's human resources in tourism management, and receiving the title of Maslahat Village. Among the obstacles is the lacking role of government elements, particularly the Tourism and Culture Agency and Community and Village Empowerment Agency.